Intencionalidad, casualidad e intermedialidad. Crítica a una historiografía de la recepción de Babel en Pieter Bruegel el Viejo y la escuela de Amberes. - Bendito, María (Eikón / Imago, 2024)
This article aims to challenge much of the literature that art history has produced on the value and meaning of Pieter Bruegel the Elder’s two towers of Babel. This critique derives from the realisation that the outcomes are critical and inadequate when, firstly, the concepts of semanticity, authorship, tradition and intentionality are subjected to crisis. Concepts that are quite common in the discipline of art history and especially weak when it intersects with the methodologies of Visual or Cultural Studies. Secondly, when these towers are studied in parallel to other images traditionally considered minor. That is to say, when we realise that historiography has considered Bruegel to be the author of novelties at the expense of other artists and media of an apparently lower status. And, finally, when the perspective from which these images should be studied and its questions are reformulated.